Strategy of Islamic Banking; A Jordanian Case Study - AbuSa'd, Yazan (2010)
This paper has attempted to tackle the difference between Islamic banks and their peer conventional banks in the area of strategic management. Five different hypotheses were hypothesized, some of which were proven and some had their null-hypothesis proven instead. The paper investigated the Jordan Dubai Islamic bank as being a case study that would represent Islamic banks functioning in the Hashemite Kingdom of Jordan, the country of our research. The research was conducted to check for the presence or absence of differences between conventional banks in areas of strategy formulation, having clear strategies, operations strategy, marketing strategy and financial strategy. All of which proven to be different from conventional to Islamic banks.